Digitization and Development of Pantok Melody Themes Tongkek Using Leon Stein's Theory Approach - Khair, Muhammad Alfian Nur (TAMUMATRA, 2023)
ABSTRACTThis paper presents a study on the composition of traditional music performance in Pancor Village, East Lombok, Indonesia with a focus on the creation of digitalized compositions based on traditional music. The study employs the approach of Leon Stein's theory of composition, which emphasizes the importance of understanding the cultural and historical context of musical works in order to create innovative and meaningful compositions.The study involves field research, where traditional music performances in Pancor Village are recorded, transcribed, and analyzed using Stein's approach to composition. The analysis focuses on identifying the characteristic elements of traditional music, such as melody, rhythm, and instrumentation, and exploring how these elements can be integrated with digital technology to create new compositions.The study also involves experimentation with digital tools, such as software synthesizers, digital audio workstations, and other music production tools, while adhering to Stein's approach to composition. These tools are used to create digitalized compositions based on the traditional music of Pancor Village, with the aim of exploring the creative possibilities of combining traditional music with modern technology, while maintaining the cultural and historical context of the original works.The results of the study show that the integration of traditional music with digital technology while employing Stein's approach to composition, can lead to the creation of innovative and compelling musical works that are relevant to contemporary audiences. The digital compositions created in this study demonstrate how traditional music can be transformed and reimagined in new and exciting ways, while still respecting the cultural and historical context of the original works.This study contributes to the ongoing conversation on the preservation and development of traditional music and demonstrates the potential of integrating traditional music with modern technology using a theoretical framework that emphasizes cultural and historical context. It also highlights the importance of understanding and respecting the cultural and historical significance of traditional music, and the role that technology can play in preserving and evolving these musical traditions.